P13 Abdominal Surgery during the COVID-19 Pandemic: A Multicentre Audit. (8th April 2021) - Hadjittofi, Christopher; Uddin, Aaliya; Seraj, Sanjid; Ali, Zeba; Antonas, Philipp; Fisher, Rebecca; Parekh, Kishan; Lovett, Bryony
Abstract: Introduction: The threshold for surgery has increased during the COVID-19 pandemic. A widely cited Chinese study (n = 34) reported postoperative COVID-19 pneumonia and mortality rates of 100% and 21% respectively [1]. This audit assessed outcomes after abdominal surgery across three hospitals within Mid & South Essex NHS Foundation Trust. Methods: Patients undergoing abdominal surgery at Basildon University Hospital, Mid Essex Hospital and Southend University Hospital between 1st March and 27th April 2020 were included. Obstetric, gynaecological, vascular, inguinal/femoral hernia, and skin operations were excluded. Electronic data collection was supplemented by telephone follow-up. Results: 306 patients were included. The median age was 57 years. 148 (48.4%) were female. 156 (51.0%) and 150 (49.0%) patients underwent elective and emergency surgery respectively. The preoperative and postoperative SARS-CoV-2 rates (based on RT-PCR or imaging) were 0.3% (n = 1) and 4.6% (n = 14) respectively. 84.6% (n = 259) did not have RT-PCR tests. All-cause 30-day mortality was 3.6% (n = 11). Amongst patients with SARS-CoV-2, mortality was 50% (7/14), occurring only after emergency surgery. Elective (vs. emergency) surgery was associated with lower postoperative SARS-CoV-2 (0.6% vs. 8.7%; p < 0.001) and mortality (0.6% vs. 6.7%; p = 0.005). At follow-up, 79.1% (242/306) of patients responded, most (85.1%; 206/242) without major clinical issue. Conclusion: Local SARS-CoV-2 and mortality rates are lower than previously reported [1]. Perioperative COVID-19 carries a high mortality risk. We recommend perioperative SARS-CoV-2 testing for all patients and cohorting by infection status. References: 1. Lei et al., Clinical characteristics and outcomes of patients undergoing surgeries during the incubation period of COVID-19 infection, EClinicalMedicine(2020), https://doi.org/10.1016/j.eclinm.2020.100331